The booming furniture industry in China - Castano, Jairo (BOIS & FORETS DES TROPIQUES, 2004)
Le résumé en français est disponible dans le fichier PDF de l'article. The high level of growth of China's furniture industry has attracted the attention of the international trade and domestic analysts. The production of furniture in China has maintained a very high growth rate for more than 20 years and furniture exports have also increased every year. (Résumé d'auteur)